Analisis Pengendalian Kualitas Proses Pengelasan (Welding) dengan Pendekatan Six Sigma pada Proyek PT. XYZ - Alfian Huda (Jurnal Wacana Ekonomi, 2018)
PT. XYZ is an offshore facility design and construction industry company that supports the activities of the oil and gas industry. Based on the project schedule data, one of the most critical processes or jobs in the implementation of a construction project is the welding process. According to welding process defect data from January to March 2017, there were found a number of defects as many as 601 welding points where every week the number of defects fluctuated. To reduce the number of defects in the welding process that occur in project implementation at PT. XYZ requires further research to identify and analyze defects. This study uses a six sigma approach consisting of DMAIC stages (Define, Measure, Analyze, Improve, Control). The Define stage is the identification stage by determining the types of defects that affect the quality of the welding process (critical to quality), namely slag inclusion, lack of fusion and porosity. Then proceed to the Measure stage, namely measuring the stability of the process and process capability, and the sigma level is obtained which is at the position of 3.21 sigma with a DPMO value of 43,958.93, besides that it is also found that there are 3 points of welding results that are outside the control limit (out of control). control), it indicates that PT. XYZ is not yet fully able to control the quality of the welding process. At the Analyze stage, several tools are used, namely cause-and-effect diagrams and FMEA analysis. Based on the results of the causal diagram, the factors that affect the defect in the welding process come from human factors, machines, methods, materials and the environment. Through the results of FMEA analysis of the five factors that affect the defect in the welding process at PT. XYZ found that, the most critical factor as the cause of the appearance of slag inclusion and lack of fusion defects is the method factor, while the porosity defect is the material factor.